Assessment of the Integration of a HIS/RIS with a PACS - Levine, Betty A. (Springer-Verlag, 2003)

(untitled)
The exchange of information between a Radiology Information System (RIS) and a PACS is essential to optimizing the utility of a PACS. Some of the benefits awarded by implementing an interface include a reduction or elimination of repetitious data entry, the availability of more accurate information on the PACS, a reduction in workload for the technologists, registration clerks, transcriptionists, etc, and the availability of more accurate data for automating the PACS. This paper discusses the Georgetown experience of interfacing an HIS/RIS and PACS, by describing the development of the interface and its impact on clinical operations.